DEVELOPMENT OF ENTREPRENEURIAL LEARNING MODEL TO INCREASE STUDENTS ENTREPRENEURS' INTEREST AT COLLEGE EDUCATION - Wesnita, Alvia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This research is based on the fact that entrepreneurship learning model has not been effective to increase student entrepreneurship interest. Referring to these conditions, this study aims to reveal and formulate entrepreneurial learning model that can increase student entrepreneurship interest. Research and development research (R & D) method by modified Borg and Gall design. The population of this research is student of Refraction Optician study program. The Data in this research is qualitative and quantitative data. This new learning model has been tested in a limited way to know the validity, practicality and effectiveness. Based on the result of the research, it is concluded that contextual based on result validity of entrepreneurship learning model, practical and effective development to increase student entrepreneurship interest. This learning model is recommended to be applied and introduced widely to similar study programs within the college.